La arquitectura teatral griega como cuerpo-red de relaciones entre el universo teatral, la polis y el mundo (Argos, 2024)
In this article, the theatrical architecture of Ancient Greece is to be considered as a body-sign that means, socially, culturally and politically constructed, as a reflection and creator of the social order, as a body that is civilization and, consequently, as a microcosm of the worldview of the ancient Greeks. And it is that the theatrical architecture is seen by the Hellenes as an articulating body, delimited, differentiated and separated and with entrances or exits that communicate their interior functions with the external ones, reason why, in spite of its autonomy, it is not isolated in itself but it constitutes a true network of relations between the theatrical universe, the polis and the world.
Keywords: sociology of the body; historical sociology; ancient Greece; theater architecture